Models of rationality: decision making in medical triage - Corbal, José A. (2021)
When making decisions, not all possible factors are always taken into account, due to the temporal limitation, either due to biased information, or even more so, the understanding of said information, or because the goals sought are adjusted to specific purposes, within a cloistered framework that may not be properly considered by the function that governs the system and determines how results are weighted, as well as by the context in which decisions take place. The choice of the correct function depends, to a great extent, on the social norms, and also on the possible sanctions that these can be given when talking about its results, so that the maximization of the beneficial results for the purpose of the function is in it struggles with minimizing those harmful to the evaluator. But in medicine, the code of ethics requires that the well-being of the patient be maximized. The ethical dilemma arises when there is a conflict between maximizing well-being and minimizing the expenditure of resources. This is where the problem of decisions arises in medical triage.